Real-Time Technique for Improving Molecular Imaging and Guiding Drug Delivery in Large Blood Vessels: In Vitro and Ex Vivo Results - Abhay V. Patil; Joshua J. Rychak; Alexander L. Klibanov; John A. Hossack (Molecular Imaging)
Ultrasound-based molecular imaging employs targeted microbubbles to image vascular pathology. This approach also has the potential to monitor molecularly targeted microbubble-based drug delivery. We present an image-guided drug delivery technique that uses multiple pulses to translate, image, and cavitate microbubbles in real time. This technique can be applied to both imaging of pathology in large arteries (sizes and flow comparable to those in humans) and guiding localized drug delivery in blood vessels. The microbubble translation (or pushing) efficacy of this technique was compared in a variety of flow media: saline, viscous saline (4 cp), and bovine blood. It was observed that the performance of this approach was marginally better (by 6, 4, and 2 dB) in viscous saline than in bovine blood with varying levels of hematocrit (40%, 30%, and 10%). The drug delivery efficacy of this technique was evaluated by in vitro and ex vivo experiments. High-intensity pulses mediated fluorophore (DiI) deposition on endothelial cells (in vitro) without causing cell destruction. Ex vivo fluorophore delivery experiments conducted on swine carotids of 2 and 5 mm cross-section diameter demonstrated a high degree of correspondence in spatial localization of the fluorophore delivery between the ultrasound and composite fluorescence microscopy images of the arterial cross sections.